PENGARUH MODEL PEMBELAJARAN PROBLEM SOLVING TERHADAP HASIL BELAJAR FISIKA SISWA KELAS VIII DI SMPN 5 LINGSAR TAHUN PELAJARAN 2012/2013 - Rahmawati Rahmawati (Universitas Pendidikan Mandalika, 2013)
This study aims to determine the Influence of Problem Solving Learning Model on Student Physics Learning Outcomes Class VIII in SMPN 5 Lingsar Academic Year 2012/2013. The type of research used is experimental research. The sample used is 21 person class VIII-A as experiment class and 23 students of class VIIIB as control class and have been determined by random sampling technique. The data in the study were obtained from initial and final tests. Data collection techniques use objective tests that have been tested for validity, reliability, distinguishing power, and difficulty indexes. The result of the data analysis obtained the average score of initial test of experimental class of 34 and 39 for control class. The final test shows an average score of the experimental class of 75 and the control class of 68. The final test data of the students of the sample class were analyzed using the t-test. Results obtained t-test of 119.61 and t-table 2.016. T-count is greater than t-table at 5% error level and db = 42. We conclude that there is a positive effect of using Problem Solving learning model to student physics learning result.